Guests of the ayatollah : the first battle in America's war with militant Islam - Bowden, Mark, 1951- (New York : Grove Press : distributed by Publishers Group West, 2006)
A chronicle of the Iran hostage crisis, America's first battle with militant Islam. On November 4, 1979, a group of radical Islamist students, inspired by the revolutionary Iranian leader Ayatollah Khomeini, stormed the U.S. embassy in Tehran. They took 52 Americans hostage, and kept nearly all of them hostage for 444 days. Journalist Bowden tells the story through the eyes of the hostages, the soldiers sent to free them, their radical captors, and the diplomats working to end the crisis. Bowden takes us inside the hostages' cells and inside the Oval Office for meetings with President Carter and his exhausted team. We travel to international capitals where shadowy figures held clandestine negotiations, and to the deserts of Iran, where a courageous, desperate attempt to rescue the hostages exploded into tragic failure.--From publisher description.
The "Set-In" -- Den of spies -- Waiting -- One hundred and thirty-two men -- Haggling with the barbarians.
Includes bibliographical references (p. [643]-656) and index.
Keywords: United States -- Foreign relations -- Iran; Iran -- Foreign relations -- United States; Iran Hostage Crisis, 1979-1981 -- Chronology; Iran Hostage Crisis, 1979-1981 -- Personal narratives; United States -- Armed Forces -- Search and rescue operations; Hostages -- Iran; United States -- Foreign relations -- Iran; Iran -- Foreign relations -- United States; Iran hostage crisis, 1979-1981 -- Chronology; Rescue work -- Iran; Iran hostage crisis, 1979-1981 -- Personal narratives; Hostages -- Iran